2022
DOI: 10.18502/japh.v7i3.10537
|View full text |Cite
|
Sign up to set email alerts
|

Source identification, spatial distribution and ozone formation potential of benzene, toluene, ethylbenzene, and xylene (BTEX) emissions in Zarand, an industrial city of southeastern Iran

Abstract: Introduction: Benzene, Toluene, Ethylbenzene, and Xylene (BTEX) as the ozone precursors have been classified as the hazardous air pollutants because of their negative effects on humans. This article presents the results of the first assessment of source identification, spatial distribution and BTEX's Ozone- Forming Potential (OFP) in Zarand. Materials and methods: The current study was conducted at 30 geographically separated locations, in Zarand, Kerman, southeastern Iran, during the summer and winter o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These results indicate that the benzene exceedance rate is high at soil sampling points, and the spatial distribution of benzene and toluene is extensive, with the pollution depth of benzene significantly influenced by the depth of groundwater. m/p-xylene < toluene [44]. Abdel-Rahman et al also demonstrated in their study benzene was one of the most detected and excessive pollutants in soil samples at t site.…”
Section: Pollution Characteristics and Spatial Distribution Of Btex I...mentioning
confidence: 77%
See 1 more Smart Citation
“…These results indicate that the benzene exceedance rate is high at soil sampling points, and the spatial distribution of benzene and toluene is extensive, with the pollution depth of benzene significantly influenced by the depth of groundwater. m/p-xylene < toluene [44]. Abdel-Rahman et al also demonstrated in their study benzene was one of the most detected and excessive pollutants in soil samples at t site.…”
Section: Pollution Characteristics and Spatial Distribution Of Btex I...mentioning
confidence: 77%
“…Malakootian et al monitored BTEX at 30 independent locations in Zarand, Kermam, southeastern Iran. The order of the detection rates for BTEX were: benzene < ethylbenzene < o-xylene < m/p-xylene < toluene [44]. Abdel-Rahman et al also demonstrated in their study that benzene was one of the most detected and excessive pollutants in soil samples at their site.…”
Section: Pollution Characteristics and Spatial Distribution Of Btex I...mentioning
confidence: 89%
“…Once in the atmosphere, its presence, influenced by meteorological conditions, contributes to the formation of smog along with other pollutants [9]. Ethylene (C2H4) is an organic compound recognized as a greenhouse gas released from plastic [10].…”
Section: Of 18mentioning
confidence: 99%
“…Benzene is a known carcinogen, and exposure to high levels of toluene and ethylene can also have health implications. Ethylene, benzene, and toluene are VOCs emitted by various sources, including vehicle exhaust, industrial activities, and natural sources such as vegetation [8,9,11,13]. At the same time, as is known, ozone is not directly emitted, rather, it forms in the atmosphere through photochemical reactions involving precursor pollutants, primarily NOx and VOCs [18].…”
Section: Atmospheric Ozone Measurementsmentioning
confidence: 99%
“…Air pollution is the presence of substances in the air in concentrations that have adverse effects on people, animals, and plants. These substances may be mixtures of solid and liquid particles (particulate matters such as PM 2.5 and PM 10 ), gases (such as NO 2 , NO, SO 2 , O 3 ), biological aerosols, or atmospheric agents biological aerosols, or atmospheric agents that can be dispersed, transported, or deformed at any time (Khafaie et al, 2016;Malakootian et al, 2022). The scale of the problem is expanding rapidly due to the high urbanization rate (Bayat et al, 2019).…”
Section: Introductionmentioning
confidence: 99%